2011
DOI: 10.1021/jp2069539
|View full text |Cite
|
Sign up to set email alerts
|

π Back-Bonding of Iron(II) Complexes Supported by Tris(pyrid-2-ylmethyl)amine and Its Nitro-Substituted Derivatives

Abstract: The electronic and geometric structures of a series of iron(II) complexes supported by tetradentate tris(pyrid-2-ylmethyl)amine-type ligands with different numbers of 4-nitropyridine groups, [(PyCH(2))(3-n)(4-NO(2)PyCH(2))(n)N] (n = 0-3), were examined by X-ray absorption fine-structure and variable-temperature (1)H NMR spectroscopies and theoretical calculations to reveal how the low-spin state is stabilized through π back-bonding interactions between iron(II) and 4-nitropyridine donor group(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Note that the latter conclusions are true under the experimental conditions of X‐ray diffraction, that is, at 100 K. A comparison of the Fe–N py bond lengths of 1 ‐(CH 3 CN) 2 and 2 ‐(CH 3 CN) 2 shows that those of 1 ‐(CH 3 CN) 2 are slightly shorter, which is consistent with a higher π‐accepting character of the 4‐nitropyridine ring with respect to the 4‐unsubstituted one. Similarly, Furukawa et al showed that the Fe–N py bond lengths in Fe II –TPA‐type [TPA = tris(pyrid‐2‐ylmethyl)amine] complexes become shorter if NO 2 groups are introduced at the para positions of the pyridine rings . They rationalized these observations on the basis of stronger π‐backbonding interactions between the Fe t 2g orbitals and the π* orbitals of 4‐nitropyridine compared with those for the unsubstituted ones.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Note that the latter conclusions are true under the experimental conditions of X‐ray diffraction, that is, at 100 K. A comparison of the Fe–N py bond lengths of 1 ‐(CH 3 CN) 2 and 2 ‐(CH 3 CN) 2 shows that those of 1 ‐(CH 3 CN) 2 are slightly shorter, which is consistent with a higher π‐accepting character of the 4‐nitropyridine ring with respect to the 4‐unsubstituted one. Similarly, Furukawa et al showed that the Fe–N py bond lengths in Fe II –TPA‐type [TPA = tris(pyrid‐2‐ylmethyl)amine] complexes become shorter if NO 2 groups are introduced at the para positions of the pyridine rings . They rationalized these observations on the basis of stronger π‐backbonding interactions between the Fe t 2g orbitals and the π* orbitals of 4‐nitropyridine compared with those for the unsubstituted ones.…”
Section: Resultsmentioning
confidence: 93%
“…Similarly, Furukawa et al showed that the Fe-N py bond lengths in Fe II -TPA-type [TPA = tris(pyrid-2-ylmethyl)amine] complexes become shorter if NO 2 groups are introduced at the para positions of the pyridine rings. [32] They rationalized these observations on the basis of stronger π-backbonding interactions between the Fe t 2g orbitals and the π* orbitals of 4-nitropyridine compared with those for the unsubstituted ones. The…”
Section: Synthesis and Solid-state Characterization Of Fe II Complexesmentioning
confidence: 85%
“…Due to the redox accessibility of iron, the Fe 3 O cluster has been noted to undergo reduction events in both MOFs, , producing a mixed valent μ 3 -oxo Fe­(III) 2 Fe­(II) cluster under a high-temperature (∼220 °C) thermal treatment. This mixed valent state is particularly important for the adsorption of certain unsaturated molecules, such as alkenes and alkynes, as the Fe­(II) sites have improved π-backdonation capabilities compared to the Fe­(III) centers. , This improved backdonation allows for a higher adsorption enthalpy at these open metal sites, thus leading to an improvement in adsorption capacity, particularly at the low adsorption pressures …”
Section: Introductionmentioning
confidence: 99%
“…This mixed valent state is particularly important for the adsorption of certain unsaturated molecules, such as alkenes and alkynes, as the Fe(II) sites have improved π-backdonation capabilities compared to the Fe(III) centers. 28,31 This improved backdonation allows for a higher adsorption enthalpy at these open metal sites, thus leading to an improvement in adsorption capacity, particularly at the low adsorption pressures. 32 These two MOFs are well known for their gas separation performance; MIL-100 has been shown to have a high affinity toward hydrocarbons such as propane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This mixed valent state is particularly important for the adsorption of certain unsaturated molecules, such as alkenes and alkynes, as the Fe(II) sites have improved π-backdonation capabilities compared to the Fe(III) centers. 28,31 This improved backdonation allows for a higher adsorption enthalpy at these open metal sites, thus leading to an improvement in adsorption capacity, particularly at the low adsorption pressures. 32 For this project the two MOFs, MIL-100 and PCN-250 were analyzed for their gas adsorption performance towards the byproducts of methane pyrolysis, with an evaluation of activation temperature showed a remarkable improvement in gas uptake, due to the production of the mixed valent states within the MOFs.…”
Section: Introductionmentioning
confidence: 99%